A case of mammary gland Carcinoma and Malignant Myoepithelioma on a female dog - Santos, M. (2008)
The mammary gland is the most commonly affected organ for tumours in the bitch. Mammary tumours mainly affect middle-aged and elderly female dogs. In this case report, a 10 year-old female mix breed dog, spayed before first heat, showed to private veterinary practice with two mammary nodules on the right mammary chain. Complete unilateral mastectomy was performed and the formalin-fixed surgical specimen was submitted to pathology service. Routine hematoxylin and eosin histhopathological evaluation was performed. On the 1st abdominal gland, the microscopic exam revealed a well circumscribed, unencapsulated nodule, compatible with lipoma. The 2nd abdominal gland showed a neoplastic spindle cell population, loosely arranged in an abundant myxoid, bluish color matrix with cartilagineous type matrix areas. These cells presented round pale nuclei, increased contour, prominent nucleoli and nuclear pleomorphism. Multinucleated giant cells and high mitotic rate were also seen. Some sections showed epithelial proliferations arranged in a tubulopapillary pattern. Since the myoepithelial component with malignant characteristics predominated as a distinct feature, the diagnosis of carcinoma and malignant myoepithelioma was established, according to Goldschmidt (2007), since this diagnosis was not possible according to previous classifications. As the myoepithelial component is benign in almost all tumours, this is considered a rare lesion in the dog. Goldschmidt M. Classification of canine mammary tumours. 2007 Davis Foundation European Symposium. University of Munich, Germany. 27-29 Aug 2007.